Deciphering the Diagnostic Potential of α-Methylacyl CoA Racemase (AMACR) in Prostatic Neoplasms: Alpha-Methylacyl CoA Racemase in Prostatic Cancer - Abbasi, Huma; Ujjan, Ikram Udin; Shaikh, Marvi; Kumari, Sandhiya; Sibghatullah, Hadiya; Memon, Maleeha (Pakistan Journal of Health Sciences, 2025)
Prostate cancer is a prevalent malignancy that affects males globally, posing a substantial impact both locally and globally. A critical marker for improving prostatic cancer diagnostic accuracy is α-Methylacyl CoA Racemase (AMACR), an enzyme involved in the metabolism of certain fatty acids and bile acid precursors. Objective: To explore the immunohistochemical expression of α-Methylacyl CoA Racemase and assess its association with the histological grading of prostatic adenocarcinoma. Methods: This retrospective cross-sectional study was carried out at Liaquat University of Medical and Health Sciences, Jamshoro between April 2023 to February 2024. Total 71 prostate cancer patients with age range of 45 to 99 years were selected for this study according to the selection criteria. The study used formalin-fixed paraffin-embedded tissue blocks for histopathology to evaluate AMACR expression through immunohistochemistry and the data was analyzed by using the Statistical Package for the Social Sciences (SPSS) for windows. Results: The immunohistochemical study revealed that 57.7% of cases showed AMACR expression, with a significant correlation between the expression levels and the tumor's histological grade (P-value < 0.05). Conclusion: The findings of this study highlighted AMACR's potential as a diagnostic biomarker for aggressive prostate cancer.